The performance of MSMEs of Gresik based on maqasid sharia - Ahmad Dahlan Malik; Andi Zulfikar Darussalam; Yanuar Trisnowati (Journal of Economics, Business, and Accountancy Ventura, 2018)
The purpose of this research is to know the performance and activity of UMKM in Gresik, East Java from maqasid syariah side, which based on the principle of maqasid syariah can give welfare (maslahah) to society wide. Therefore, whether the performance and activities undertaken by SMEs according to the principles of maqasid syariah especially SMEs in Gresik. Micro, small and medium enterprises (MSMEs) are business actors that directly touch the community so that it has a very important role in the absorption of manpower and regional income and the economy widely. Although MSMEs have fundamental problems mainly on internal and external issues such as limited capital, human resources, business network and market penetration, business climate, facilities and infrastructure, short life time product, market access, and free trade. This research was conducted in three stages. The first phase of the exploration aims to provide initial insight, research design, and test theoretical framework through pilot study and interview on UMKM Gresik. The second phase is a survey of MSME Gresik to form the basis of generalization. And the third stage is a case study on SMEs Gresik sample to explore relationships and relevant results on the performance and activities of MSMEs with maqasid sharia.